Characterization of a Plastoglobule-Localized SOUL4 Heme-Binding Protein in Arabidopsis thaliana - Shanmugabalaji, Venkatasalam; Grimm, Bernhard; Kessler, Felix (Frontiers in Plant Science, 2020)
Heme plays an active role in primary plant metabolic pathways as well as in stress signaling. In this study, we characterized the predicted heme-binding protein SOUL4. Proteomics evidence suggests that SOUL4 is a component of Arabidopsis plastoglobules (PG, chloroplast lipid droplets). SOUL4 contains heme-binding motifs and the recombinant protein is shown here to bind heme in vitro. Fluorescence-tagged SOUL4 colocalized with the specific PG marker FIBRILLIN1A (FBN1A) in transiently transformed Nicotina benthamiana leaves. In addition, SOUL4 cofractionated with another PG marker FIBRILLIN2 (FBN2) in sucrose gradient ultracentrifugation experiments. In vitro kinase experiments revealed that SOUL4 is phosphorylated by a yet unknown chloroplast protein kinase. Our data demonstrate that SOUL4 is a bona fide plastoglobule protein and may function in heme-buffering in the chloroplast.